1997
DOI: 10.1002/(sici)1097-0010(199711)75:3<371::aid-jsfa890>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irradiation on vitamin C content of strawberries and potatoes in combination with storage and with further cooking in potatoes

Abstract: The vitamin C content of four varieties of strawberry was determined before and after treatment with ionising radiation at doses of 1, 2 or 3 kGy and after storage for 5 and 10 days at 6°C, and also in potatoes which, having been allowed a period of one month to recover from the effects of post‐harvest stress, were irradiated at a sprout inhibition dose of 0·15 kGy, followed by storage and cooking. Total ascorbic acid (TAA), ascorbic acid (AA) and dehydroascorbic acid (DHAA) concentrations were measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Ascorbic acid and dehydroascorbic acid were analyzed using modifications of the method of Graham and Stevenson (1997). The juice (5 ml) was homogenized for 3 min with an equal volume of 2.5% metaphosphoric acid and was centrifuged for 5 min at 6500g.…”
Section: Nutritional Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…Ascorbic acid and dehydroascorbic acid were analyzed using modifications of the method of Graham and Stevenson (1997). The juice (5 ml) was homogenized for 3 min with an equal volume of 2.5% metaphosphoric acid and was centrifuged for 5 min at 6500g.…”
Section: Nutritional Analysissupporting
confidence: 88%
“…The decrease observed in the total ascorbic acid was less than that of the ascorbic acid due to the amount of dehydroascorbic acid which may converted from ascorbic acid. This result was similar to the results from the analysis of potato samples which showed that the dehydroascorbic acid content increased immediately following irradiation (Graham & Stevenson, 1997). During the storage period, total ascorbic acid, ascorbic acid, and dehydroascorbic acid contents were reduced (P < 0.05), and the ascorbic acid of the irradiated carrot and kale juice were higher than that of the non-irradiated at 3 days of storage.…”
Section: Nutritional Quality Of Irradiated Vegetable Juicementioning
confidence: 99%
“…In general doses of 2-3 kGy combined with refrigeration were useful for extending the shelflife of strawberries (Graham and Stevenson, 1997). During storage AA levels significantly intrimming of leafy vegetables results in loss of outer green leaves which contain more vitamins than inner leaves.…”
Section: Irradiationmentioning
confidence: 99%
“…Dehydrated pineapples and guava pretreated with cysteine hydrochloride had increased AA retention and reduced color change during storage (Mohamed et al, 1993). Table 7 Effect of irradiation dose and storage on the total AA (TAA), reduced AA (RAA), and DHA concentrations (mg/100g FW) of strawberry (Graham and Stevenson, 1997) Table 8 AA content (mg/100g FW) of apples (Zubeckis, 1962) (Table 9). The total vitamin C was 8, 13, or 21% lower than initial values in slices kept for 6 days at 0, 5, or 10°C, respectively (Agar et al, 1999).…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…The AACs were determined according to the method of Graham and Stevenson (1997). The green tea (1 mL, 1 mg/mL) was centrifuged at 10,000 × g for 10 min and the supernatants (0.5 mL) were mixed with 2 mL of trichloroacetic acid (5%), after which the mixtures were centrifuged at 15,000 × g for 10 min (4C).…”
Section: Methodsmentioning
confidence: 99%